Aspri, Maria - (:unkn) unknown (My University, 2026)
Maria Aspri has a BSc in Food Science and Microbiology from University of Surrey (UK) and a research MSc in Food Microbiology from the University College of Cork in Ireland. She obtained her PhD at the Dairy Science and Technology Laboratory at Cyprus University of Technology. Her PhD thesis was on the isolation and identification of beneficial Lactic Acid Bacteria from donkey milk, in order to be used as starter/ adjunct cultures for the production of a functional fermented donkey drink (probiotic, ACE-inhibitory, antimicrobial and antioxidant activity), followed by the peptidomic profile of raw and fermented donkey milk after in-vitro [...]digestion. Furthermore, she was a post doc researcher at the Department of Agricultural Sciences, Biotechnology and Food Science of CUT. She also worked as a Quality Control Manager for a private food and water testing laboratory. Her main research interests includes the development of novel functional food products in particular with probiotic bacteria, their functional properties and the production of bacteriocins and bioactive peptides after in-vitro digestion process. Furthermore, she is working with the application of non-thermal treatments (UV-C) and their effect on the microbiological and nutritional quality of the final product.
Keywords: agric; In-vitro digestion; lactic acid bacteria; bacteriocins; probiotics; functional properties; non-thermal treatments